Experimental colonization of broiler chicks with Campylobacter jejuni. - Shanker, S. (Cambridge University Press, 1988)
Minimal colonization inocula for two broiler strains of Campylobacter jejuni were determined in broiler chicks aged 2-3 days and 2 weeks. Individually housed chicks were exposed to a single oral or cloacal challenge. Diarrhoeal symptoms were absent in all 380 chicks included in the study. Chick susceptibility to the two C. jejuni strains varied. Colonization was effected by less than 10(2)-10(4) colony forming units (c.f.u.) via cloacal challenge and 10(4)-10(6) c.f.u. via the oral route. Colonization inocula for 2- to 3-day and 2-week-old chicks were similar. Treatment of 1-day-old chicks with fresh adult caecal flora or an anaerobic broth culture of adult caecal flora did not inhibit colonization after challenge with low-dose C. jejuni. Susceptible chicks were colonized rapidly. C. jejuni was detected in 167 of 189 (88%) colonized chicks within 3 days of challenge and persisted during the 2-week monitoring period. Our data suggest that colonization of broiler chicks with C. jejuni is effected more easily by the cloacal than the oral route and is independent of age.